PENERAPAN METODE EKSPERIMEN PADA MATERI STRUKTUR DAN FUNGSI TUMBUHAN SEBAGAI UPAYA PENINGKATAN HASIL BELAJAR SISWA SMP - Tety Surtiningsih (Journal of Social Studies Arts and Humanities (JSSAH), 2022)
APPLICATION OF EXPERIMENTAL METHODS ON MATERIAL STRUCTURE AND FUNCTION OF PLANTS AS AN EFFORT TO IMPROVE LEARNING OUTCOMES OF JUNIOR HIGH SCHOOL STUDENTSThis research is motivated by learning outcomes in science subjects achieved by students of class VIII Junior High School, the results of the material structure and function of plants are unsatisfactory, there are still many students' scores that are still below the Minimum Completeness Criteria. This could be due to the teacher still using the lecture method at the time of learning. Another cause of time constraints causes learning to refer to the transfer of knowledge to pursue curriculum targets. This research is classroom action research with the model of Stephen Kemmis and Robbin Mc Taggart. After doing research actions, it can be concluded that the ability of students to solve problems on the material structure and fungi of plants through the use of experimental methods can actually increase the interest, enthusiasm, concentration, and activeness of students in the learning process. In addition, there is also an increase in learning outcomes in the form of an increase in the average value of the class and an increase in the percentage of students' learning completeness individually and classically for students. Thus, based on the results of this study, it was concluded: 1) the use of experimental methods can improve student learning outcomes, 2) the use of experimental methods in learning makes students not bored and bored on the contrary feel happy so that their learning activities increase, this is evident in the seriousness aspect There was an increase in the percentage of students in taking lessons from the first cycle to the second cycle, namely 82% in the first cycle to 95% in the second cycle, and 3) learning mastery increased, at the pre-cycle time 56.25% after using the experimental method increased in the first cycle to 75.00% and the first cycle to 100.00%.